International perspectives on psychotherapy (Springer International Publishing, 2017)
This clear-sighted resource critically examines the status of clinical psychology practice across the diverse regions of the world. Dispatches from North and Latin America, Eastern and Central Europe, China, South Korea, Australia, Africa, the Middle East, and elsewhere illustrate in depth the universality of mental distress and disorders, and the intersection of local knowledge and established standards in providing effective care. Pathology and its treatment are viewed in light of cultural values, belief systems, ethics, and norms, reflecting the evolution of clinical practice toward personalized care and culturally sensitive intervention. This important information serves a number of immediate and long-term goals, including developing culture-specific diagnoses and treatments, improving professional competencies, and the ongoing exchange of ideas within a global field to benefit all patients worldwide. Coverage compares key areas such as: ? Concepts of mental pathology and health. ? The sociopolitical aspects of psychology, rooted in the history of the country/region. ? Popularly used approaches to intervention. ? Types of services and providers. ? The state of training and credentialing. ? Relationships between clinical psychology and indigenous healing traditions. The audience for Clinical Psychology across the World includes advanced undergraduate and graduate students and trainees/interns in clinical psychology, as well as developers of training programs. It can also serve asa valuable supplementary text for seminars or lectures on clinical psychology.